Sob o signo de Judas: reescritas literárias da traição - Kesia Rodrigues de Oliveira (2016)
This dissertation lists some literary rewritten literary texts from the biblical episode of Judas, the one who betrayed Jesus, narrated in the Gospels of Matthew, Mark, Luke and John, and also in the apocryphal Gospel of Judas, and takes into account two textual construction strategies, which are paraphrase and parody. Taking as a reference the theoretical studies on intertextuality, by Julia Kristeva and Antoine Compagnon, this study aims at understanding in what ways Judas configure himself as a metaphor of literary appropriation, since the texts analyzed in this study, such as the play O Judas em Sábado de Aleluia, 1846, by Martins Pena, the chronicles Judas, 1921, by Graciliano Ramos, and Malhação do Judas Carioca, 1975, by João Antônio, lead to literature or rewritten literary texts, as a means of betrayal.